Implementation of Character Education in Online Learning - Eliza Verdianingsih; Leli Ramadani Ida (APPLICATION: Applied science in Learning Research, 2021)
Character education is a student's personality to become a better person. Both among schools and among the community, and these students also need to be taught to have good morals in the future. During the pandemic, the current implementation of learning is carried out online so that students will not miss lessons. Character education in online learning at MA Nizhamiyyah has a vision and mission, one of which is to create superior students in the fields of science and technology, to create superior students in the fields of skills, creativity, independence and to educate superior students in the fields of faith and piety. This study aims to describe the character education in learning from MA Nizhamiyah in the subject of Fiqh. The research method used in this research is a qualitative method with data collection techniques using questionnaires, interviews, documentation. The results of this study indicate that character education in online learning in Fiqh subjects at MA Nizhamiyyah has been implemented by fiqh teachers ranging from religious values, honesty, tolerance, discipline, hard work and creativity. While the implementation of online learning in fiqh subjects at MA Nizhamiyah starts from the quality of learning, alignment with learning objectives, feedback, online learning techniques and learning facilities. This research can be useful for teachers to add references on how to build character for students. The benefits of research for students are to provide knowledge and insight to them about the importance of character education for themselves as learners.